Storage life extension of 'Sai Nam Pueng' tangerine fruit by using three different coating materials - W. Kumpoun (2018)
The effects of coating materials on quality changes and shelf life of tangerine 'Sai Nam Peung' fruit during storage were investigated. Three types of coating materials were used including A: oxidized polyethylene shellac and wood resin; B: oxidized polyethylene and shellac; and C: shellac, to coat tangerine fruit with non-coated fruit as controls. Fruit were stored at 5°C; samples from each treatment were removed from storage after 0, 10, 20, 30 and 40 d and placed at 25°C. Fruit quality attributes and shelf life were measured every 2-day. Non-coated fruit showed signs of wilting after 8 d at room temperature, while fruits coated with material A did not wilt but developed abnormal odor after 16 d. After 18 d, fruit coated with coating material C developed abnormal odor and were also slightly wilted. Storing fruits at 5°C on various numbers of d gave different results. Non-coated fruit showed wilting after 20 d. Significant weight loss occurred in fruit taken from 5°C to 25°C although no abnormal odor could be observed through the storage. Coated fruits with each of the coating materials retained acceptable quality for more than 40 d at 5°C, with no wilting occurring and no abnormal odor developing. However, the longer the fruits were kept at 5°C, the shorter the shelf life of fruit when removed to 25°C.